Gonioscopy-assisted Transluminal Trabeculotomy: An Ab Interno Circumferential Trabeculotomy. Issue 5 (May 2018) - Grover, Davinder S.; Smith, Oluwatosin; Fellman, Ronald L.; Godfrey, David G.; Gupta, Aditi; Montes de Oca, Ildamaris; Feuer, William J.
Abstract : Purpose: The purpose of this study was to provide 24-month follow-up on surgical success and safety of an ab interno circumferential 360-degree trabeculotomy. Methods: Chart review of patients who underwent a gonioscopy-assisted transluminal trabeculotomy (GATT) procedure was performed by 4 of the authors (D.S.G., O.S., R.L.F., and D.G.G.). The surgery was performed in adults with various types of open-angle glaucoma with preoperative intraocular pressures (IOPs) of ≥18 mm Hg. Results: In total, 198 patients aged 24 to 89 years underwent the GATT procedure with at least 18 months follow-up. Patients with primary open-angle glaucoma had an average IOP decrease of 9.2 mm Hg at 24 months with an average decrease of 1.43 glaucoma medications. The mean percentage of IOP decrease in these primary open-angle glaucoma groups at 24 months was 37.3%. In secondary open-angle glaucoma, at 24 months there was an average decrease in IOP of 14.1 mm Hg on an average of 2.0 fewer medications. The mean percentage of IOP decrease in the secondary open-angle glaucoma groups at 24 months was 49.8%. The cumulative proportion of failure at 24 months ranged from 0.18 to 0.48, depending on the group. In all 6 study groups, at all 5 postoperative time points (3, 6, 12, 18, and 24 mo) the mean IOP and reduction in glaucoma medications was significantly reduced from baseline ( P <0.001) with the exception of one time point. Conclusions: The 24-month results demonstrate that GATT is relatively safe and effective in treating various forms of open-angle glaucoma. The long-term results for GATT are relatively equivalent to those previously reported for GATT and ab externo trabeculotomy studies.